ON THE CULTURAL AND HISTORICAL HERITAGE OF SHUMEN FROM THE XIX CENTURY AND ON THE ECONOMIC AND TECHNOLOGICAL INNOVATIONS IN THE CITY: ON THE CULTURAL AND HISTORICAL HERITAGE OF SHUMEN FROM THE XIX CENTURY AND ON THE ECONOMIC AND TECHNOLOGICAL INNOVATIONS IN THE CITY - Georgieva, Milena (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
During the period XV – XIX century, Shumen was an important administrative center in the Ottoman Empire because of its strategic location, favorable weather and its natural defenses. In the 19th century, the residents of Shumen had the opportunity to develop modern trade, crafts, to apply technological innovations in their manufacturing, to improve the economy and the everyday lives of its population.